Experiences of water immersion during childbirth: a qualitative thematic synthesis - E. Reviriego-Rodrigo; N. Ibargoyen-Roteta; S. Carreguí-Vilar; L. Mediavilla-Serrano; S. Uceira-Rey; S. Iglesias-Casás; A. Martín-Casado; A. Toledo-Chávarri; G. Ares-Mateos; S. Montero-Carcaboso; B. Castelló-Zamora; N. Burgos-Alonso; et al. (BMC, 2023)
Abstract Background The increasing demand for childbirth care based on physiological principles has led official bodies to encourage health centers to provide evidence-based care aimed at promoting women's participation in informed decision-making and avoiding excessive medical intervention during childbirth. One of the goals is to reduce pain and find alternative measures to epidural anesthesia to enhance women's autonomy and well-being during childbirth. Currently, water immersion is used as a non-pharmacological method for pain relief. This review aimed to identify and synthesize evidence on women's and midwives' experiences, values, and preferences regarding water immersion during childbirth. Methods A systematic review and thematic synthesis of qualitative evidence were conducted. Databases were searched and references were checked according to specific criteria. Studies that used qualitative data collection and analysis methods to examine the opinions of women or midwives in the hospital setting were included. Non-qualitative studies, mixed-methods studies that did not separately report qualitative results, and studies in languages other than English or Spanish were excluded. The Critical Appraisal Skills Program Qualitative Research Checklist was used to assess study quality, and results were synthesized using thematic synthesis. Results Thirteen studies met the inclusion criteria and were included in this review. The qualitative studies yielded three key themes: 1) reasons identified by women and midwives for choosing a water birth, 2) benefits experienced in water births, and 3) barriers and facilitators of water immersion during childbirth. Conclusions The evidence from qualitative studies indicates that women report benefits associated with water birth. From the perspective of midwives, ensuring safe water births requires adequate resources, midwives training, and rigorous standardized protocols to ensure that all pregnant women can safely opt for water immersion during childbirth with satisfactory results.